Frequency of post-traumatic osteoarthritis in dogs after repair of a humeral condylar fracture - Gordon, W. J.; Besancon, M. F.; Conzemius, M. G.; Miles, K. G.; Kapatkin, A. S.; Culp, W. T. N. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The frequency of post-traumatic osteoarthritis (PTO) in the dog after repair of a humeral condylar fracture (HCF) and the relationship of fracture reduction to outcome is unknown. The objectives of this study were to determine the frequency of PTO in dogs after HCF repair and to determine the relationship between fracture reduction, limb function and follow-up osteoarthrosis (OA) score. All dogs were evaluated by physical and radiographic examinations and dogs with unilateral fracture repair were also examined by force platform gait analysis. Initial and follow-up radiographs were scored for reduction and evidence of osteoarthrosis using previously published grading scales. This study evaluated 15 fractures in 13 dogs with a mean follow-up time of 43 months. Osteoarthrosis developed or progressed radiographically in all elbows. Peak vertical force (PVF) was significantly reduced (p <0.01) in the affected limb, however vertical impulse (VI) did not differ (p = 0.12) when compared to the opposite normal limb. Pain-free range of motion was reduced in flexion (p <0.01), but not in extension (p = 0.98) when compared to the normal limb. Fracture reduction score did not correlate with follow-up OA score (p = 0.07), PVF (p = 0.40), VI (p = 0.72), flexion (p =0.50), or extension (p = 0.62). Due to the high incidence of PTO, owners should be warned of the possibility of declining limb function over time despite near anatomic reduction.
Keywords: Humeral condylar fracture; post traumatic osteoarthritis; elbow arthritis; articular fracture; fracture reduction